The impact of digital transformation on systemic risk in the banking industry - Chen, Lian (SHS web of conferences, 2024)
In recent years, national strategies have accelerated digital transformation across various sectors, and for the banking industry, effectively managing risks in the digital era is essential for ensuring stable growth. This project aims to examine how digital transformation in banks influences systemic risk within the banking sector. It utilizes SRISK, based on the conditional mean method, as an indicator of systemic risk in banking, along with digital transformation indices derived from data collected by Peking University (2010-2021) and additional data from 2022 and 2023. The study investigates the effects and mechanisms through which banking digital transformation impacts systemic risk, focusing on both internal generation and contagion mechanisms. By analyzing the interactions between digital adoption and financial stability, the research sheds light on potential vulnerabilities that may arise from rapid technological advancements. It also provides policy recommendations for commercial banks and regulatory authorities to help mitigate systemic risks and enhance theoretical frameworks related to banking digital transformation.